Komunikasi Pembelajaran Pendidikan Islam Moderat Dalam Podcast “Log In Season 2” Oleh Habib Ja’far - Muhammad Ariful Hakim; Saeful Anam (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study is driven by the urgency of promoting religious moderation in Indonesia’s pluralistic society, where religious polarization remains a persistent challenge. It focuses on the digital preaching of Habib Ja’far through Podcast Log In Season 2 on YouTube, exploring how his unique communication style conveys messages of moderate Islam. The central research question is: How does Habib Ja’far’s communication of Islamic education, grounded in a religious moderation perspective, manifest in digital content, and what theoretical and practical strategies underlie its effectiveness? Employing a qualitative approach and descriptive content analysis, the study analyzes selected episodes from Podcast Log In Season 2 specifically episodes 9, 15, 17, 24, 27, and 30 based on their thematic relevance to religious moderation and high audience engagement. Primary data were collected through video documentation and in-depth interviews with informants, including Islamic communication experts, digital media observers, and selected viewers. Data validation was ensured through methodological triangulation comparing interview findings, video analysis, and related secondary sources. This study applies Islamic education communication theory alongside Peter L. Berger and Thomas Luckmann’s theory of social construction to examine how digital religious messages are constructed, contextualized, and disseminated. The findings reveal that Habib Ja’far’s communication strategies incorporate dialogical methods, humor, everyday analogies, and culturally resonant storytelling. These techniques promote values of inclusivity, tolerance, and critical engagement with religious extremism. This study contributes to the discourse on Islamic education and digital da’wah by highlighting how adaptive communication strategies can effectively promote religious moderation in online spaces. Practically, the findings offer insights for educators, preachers, and policymakers on leveraging digital media for value-based education. Future research could explore audience reception across different platforms or conduct comparative studies with other digital preachers in Southeast Asia.